Identity at Your Fingertips: The Erosion of Sundanese Culture in the Unstoppable Flow of Digitalization - Gunawan Gunawan; Jajang Hendar Hendrawan; Feni Awati Darmana (Global Education Journal, 2026)
Digitalization has become a transformative force that has fundamentally changed the social, cultural, and educational patterns of modern society. In Indonesia, particularly among the Sundanese people, the massive wave of digitalization poses a serious challenge in the form of erosion of local cultural identity due to the dominance of a homogeneous and instant global culture. This phenomenon has a significant impact on the younger generation who grow up in a digital ecosystem and are potentially experiencing cultural identity disorientation. This study aims to analyze digitalization as an accelerating factor in the erosion of Sundanese cultural identity and to examine the strategic role of education in preserving and revitalizing this cultural identity in the digital age. The research method used is a qualitative approach with a library research study through the analysis of various scientific sources, educational policy documents, and statistical data related to digitalization and culture. The results of the study show that the high penetration of the internet and the dominance of global digital culture accelerate the erosion of the Sundanese language, values of collectivism, and local wisdom among the younger generation. Education has a central role as the last bastion in preserving cultural identity through the integration of local values into the curriculum, particularly through the Merdeka Curriculum and the Pancasila Student Profile Strengthening Project. The creative and ethical use of digital technology based on local wisdom has proven to be an important strategy for shaping a digitally literate generation that is also deeply rooted in culture, because a great nation is one that is able to preserve and nurture its culture amid changing times.